PENERAPAN KOMUNIKASI TERAPEUTIK OLEH BIDAN KEPADA IBU HAMIL DALAM KEGIATAN ANTE NATAL CARE DI PUSKESMAS JELAPAT KECAMATAN MEKARSARI KABUPATEN BARITO KUALA - Helmi Helmi (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2018)
Therapeutic communication is the ability or skill of health workers to help clients adapt to stress, overcome pathological disorders and learn how to connect with others. Therapeutic communication activities mean interaction to facilitate help overcome health problems. The purpose of therapeutic communication to develop the personal client / patient towards a more positive.This research uses descriptive method of qualitative approach intended to describe, describe, and describe in detail about therapeutic communication form conducted by midwife in orientation phase, working and termination phase and exploring support factor and inhibiting of communication therapeutic to patients in the care of Antenatal care. While the pregnant mother's patients conducted in-depth interviews after receiving Antenatal care service.The results obtained, the process of Antenatal services at Puskesmas Jelapat Barito Kuala District is in accordance with antenatal care standards that is guided by 10 T. Therapeutic communication conducted midwives to pregnant women patients in providing services Antenatal care at Puskesmas Jelapat Barito Kuala District. therapeutic communication forms performed by the midwife either at the stage or the initial phase (orientation), the working stage and termination stage is interpersonal communication through verbal, written, and nonverbal message delivery. Midwives can identify and describe supporting and inhibiting factors in therapeutic communication. The patient's assessment is conceptually impaired but the patient benefits from therapeutic communication.Suggestion; quality health service needs awareness of Puskesmas Jelapat about the importance of therapeutic communication, all midwives in Puksesmas Jelapat to improve skill or ability in communicating with patient, Puskesmas Jelapat suggested make SOP which firmly, evaluative and responsive especially for therapeutic communication service implementation, preparing a draft of Therapeutic Communication SOP in the ANC service to be submitted to the Puskesmas Leadership Keywords: Therapeutic Communication, Midwife. Pregnant Women, Antenatal Care (ANC)